Major vascular events after first incident stroke: a population-based study - Charles D A Wolfe; Abdel Douiri; Rayka Malek; Salha Alasiri (BMJ Neurology Open)
Background Recent advances in stroke care have led to improvements in survival and rates of stroke recurrence. However, there is a lack of data on trends of major vascular events, and risk factors associated with non-fatal and fatal outcomes. We aim to identify demographical and clinical factors leading to incidence of subsequent major vascular events after the first-ever stroke.Methods 6051 patients’ records with first-ever stroke between 1995 and 2018 in South London, UK were analysed. Semicompeting risks models were constructed to estimate factors affecting time to incidence of recurrent stroke, myocardial infarction (MI), mortality and transitions from poststroke recurrence/MI to mortality (indirect mortality). Cumulative incidence functions were plotted for each major vascular event, stratified by stroke subtypes. All models were adjusted for age, sex, socioeconomic status, comorbidities, stroke severity and stroke subtype.Results Five years of cumulative incidences were 9.2% (95% CI (8.4% to 10.0%)) for recurrent stroke, 4.4% (95% CI 3.9% to 5.0%) for MI, and 45% (95% CI 44% to 47%) for mortality. Prior atrial fibrillation was associated with 47% increased risk of mortality (HR=1.47 (95% CI 1.23 to 1.75)) and a previous diagnosis of MI was the strongest risk factor for poststroke MI (HR=9.17 (95% CI 6.28 to 13.39)). Stroke unit was associated with a 40% lower hazard of mortality without having a recurrent stroke/MI (HR=0.60 (95% CI 0.50 to 0.72)) and a 39% lower hazard of indirect mortality (HR=0.57 (95% CI 0.37 to 0.87)).Conclusion Major vascular events are prevalent after stroke, particularly among those with concurrent vascular conditions. The rate of stroke recurrence plateaued in the last decade, yet MI incidence increased. Targeted strategies to control risk factors are required to reduce the incidence of a second vascular event and prevent progression to mortality in these high-risk groups.